Relationship between investment and sports results of Spain and the United Kingdom in the last 20 years (1996-2016) - González-Ruiz, J.; Torres-Luque, G.; Roca-Cruz, A.; Puga González, E.; Cabello-Manrique, D. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2018)
The purpose of this article is to analyze how economic cycles affect investment in Sport Federations and their international sport results. This study analyzes the models of Spain and the United Kingdom to establish a starting point for change and to identify a model to follow. A sample ofthe Olympic games during the last 20 years of both countries was taking (Sidney 2000; Athens 2004; Beijing 2008; London 2012 and Rio 2016). The results show how Spain has been decreasing public investment in sports since the crisis, although maintaining its sport results. This shows an improvement of public resources and its own resources. UK shows a much stronger economic recovery, which has boosted its sports results as it has almost double the medal number in the post crisis period. There is a greater effectiveness and efficiency of the UK model that needs to send less than half Olympic athletes to get excellent results, generating a medal cost per inhabitant 50% lower than Spain.